2007
DOI: 10.1111/j.1475-2743.2007.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

A critical examination of some common field tests to assess the acid‐sulphate condition in soils

Abstract: Acid-sulphate soils are of major environmental concern in many wetlands. Severe acidification episodes have occurred worldwide because of the oxidation of iron sulphides to sulphuric acid by human activities, and diverse techniques have been set up to determine the presence of acid-sulphate soils. This paper evaluates the usefulness of four common easy-to-apply field survey tests for potential acidsulphate diagnosis in some Histosols and Entisols in wetlands: incomplete oxidation by fast air-drying, incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In places where ASS are present, appropriate management practices need to be employed to minimize soil oxidation and acid production (Vegas‐Vilarrubia et al ., ; Melville & White, ). Strategies focusing on two key principles have been proposed, tested and established (Baldwin & Fraser, ).…”
Section: Introductionmentioning
confidence: 99%
“…In places where ASS are present, appropriate management practices need to be employed to minimize soil oxidation and acid production (Vegas‐Vilarrubia et al ., ; Melville & White, ). Strategies focusing on two key principles have been proposed, tested and established (Baldwin & Fraser, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, this process is demonstrated by the high correlations between the SO 4 2content, pH values, and ECe ( Figure 7). The observed low soil pH values and the soluble sulfate contents (SO 4 2-) also indicated acid-sulfate soil potential (Vegas-Vilarrúbia et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…[ 35 , 36 ], a simple field test on sulfide materials is as follows: after applying 30% hydrogen peroxide to the fresh sample, within a couple of minutes, it will froth and its pH will fall from neutral to less than 2.5. Although in general, pyrite oxidation generated acidity and proceeded faster in mineral samples [ 37 ], note that the hydrogen peroxide test was not effective for soils with high organic matter content because acidity may have been generated by the oxidation of organic matter to organic acids [ 35 , 37 ], which leads to lower pH values.…”
Section: Discussionmentioning
confidence: 99%